2017
DOI: 10.21786/bbrc/10.3/2
|View full text |Cite
|
Sign up to set email alerts
|

Resilience and basic psychological needs among Palestinian school students

Abstract: The purpose of this study is to explore the relationship between Basic Psychological Needs including Autonomy, Competence and Relatedness (Deci and Ryan, 2000) and factors predicting resilience (American Psychological, 2010) among Palestinian school students who are living under adversity in the West Bank. The participants were 537 students 13 and 14 years old (45% male and 55% female) representing both urban and rural areas of the northern West Bank. All participants completed the CYRM-28 Psychological Resili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 0 publications
3
8
0
Order By: Relevance
“…This is an ethical, moral, and religious commitment. These findings are consistent with Abualkibash and Lera Rodríguez (2017) who found that resilient children are empowered or self-determined.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This is an ethical, moral, and religious commitment. These findings are consistent with Abualkibash and Lera Rodríguez (2017) who found that resilient children are empowered or self-determined.…”
Section: Discussionsupporting
confidence: 92%
“…This is an ethical, moral, and religious commitment. These findings are consistent with Abualkibash and Lera Rodríguez (2017) who found that resilient children are empowered or self‐determined. They also confirmed that empowered children display greater resilience, self‐determination, power, control, ability, competence, self‐efficiency, autonomy, knowledge, and development.…”
Section: Discussionsupporting
confidence: 91%
“…They self-regulate by planning for and setting goals and then monitoring their progress toward these goals. The satisfaction of basic psychological needs, facilitated by supportive social contexts, appears both to foster a sense of wellness and to lead to building inner resources that underlie resilience [48].…”
Section: Self-determination Theorymentioning
confidence: 99%
“…Competence need refers to the perception that one is capable of achieving the desired goals [ 17 ]. It has been found to be significantly and positively correlated with resilience [ 24 , 25 ]. Neufeld and Malin have suggested that competence need satisfaction is associated with an increase in college students’ resilience and it likely represents a valuable avenue for supporting resilience [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…Relatedness need is the belief that one is connected and valued by others [ 17 ]. It has been reported to be closely related to psychological resilience [ 24 , 31 ]. Rutter has suggested that when an individual develops positive and close relationships with others, a strong social support system will be created for dealing with adversity [ 35 ].…”
Section: Introductionmentioning
confidence: 99%